PENERAPAN STRATEGI CARD SORT DALAM MENINGKATKAN HASIL BELAJAR PADA MATA PELAJARAN IPA SISWA KELAS IV SD NEGERI 2 SUBULUSSALAM - Putri Rahmatullaili; Mawar Sari (Trigonometri: Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The results of this research show that the application of the card sort strategy has been successful in improving student learning outcomes in science subjects, this is proven by the percentage of completeness of student learning outcomes which previously in the pre-test was only 31.81% where 7 students were declared complete. students with an average score of 55.45%. Furthermore, in the results of cycle I, the percentage of completeness of student learning outcomes increased by 63.63% with an average score of 68.63%, where 14 students experienced completeness. In cycle II, the card sort strategy was applied again and the percentage of completeness of student learning outcomes increased by 86.36% with an average score of 81.81% where 19 students were declared complete and 3 other students did not complete. Teacher activity also improved for the better after using the card sort strategy in the fourth grade science subject at SD Negeri 2 Subulussalam. In cycle I, the score obtained by the teacher was 28 with a completion percentage of 77.77%. Meanwhile, in the second cycle, the teacher's ability to manage learning in the classroom by implementing the card sort strategy had reached a score of 35 with a completion percentage of 97.22%. This shows that the percentage of completeness achieved by the teacher is very good, therefore this research can be said to have been successful.